A pseudo-elasticity theory to model the strain-softening behavior of tough hydrogels. (April 2020) - Lu, Tongqing; Wang, Zhongtong; Tang, Jingda; Zhang, Wenlei; Wang, Tiejun
Abstract: Rubber-like soft materials can be modeled by the statistical behavior of polymer chains and the network theory within the framework of thermodynamics. For example, the freely jointed chain model describes the deformation behavior of a single chain and the eight-chain network model relates the chain behavior to the macroscopic deformation. The emerging soft hydrogel materials with superior toughness contain additional constituents rather than one polymer network and thus have complex interplays when subject to external forces. For the double-network hydrogels, the existence of a second sacrificial network, serving as a source of energy dissipation, makes the stress-stretch curves exhibit a strain-softening behavior, which cannot be modeled by the freely jointed chain model. In this work, we develop a constitutive model for the strain-softening behavior of tough hydrogels. We introduce an internal variable to the free energy function of a single chain and then map the deformation of chains to the macroscopic deformation of polymer network. We synthesize different kinds of tough hydrogels and conduct uniaxial tension experiments. We demonstrate that the present model has a wide range of tunability and is capable of modeling the quasi-static tension of tough hydrogels with different chemical compositions, the irreversible damage behavior of chemically crosslinked hydrogels, the recoverable behavior of physically crosslinked hydrogels, the Mullins effect and the rate-dependent behaviors. These results enrich the large deformation theory and extend the classical constitutive models to capture the new features in the emerging soft and tough materials.